El mal diseño del mobiliario, causa de trastornos musculo esqueléticos en la población escolar, una aproximación al estado del arte (2009)
The purpose of this article is a review of the literature presents on the evil design of the furniture, reason of disorders muscle skeletal in the school population. Here one tries to identify the possible alterations muscle skeletal that can generate in the pupils caused by an evil design of the school furniture for such a motive followed some phases proposed by Consuelo Hoyos Botero to reach a goal of work. In the first phase of the state of the art, comprise the initial studies with reference to the topic at hand, and the thematic clusters. In the descriptive phase comprises the arduous task of locating the equipment and the sources from which it will draw all possible information after being selected, is the interpretation by thematic focus, which are defined in three categories: design ergonomic seated posture and musculoskeletal disorders, the 3 under furniture.